(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article explores the role of biotechnology in water resource management, focusing on wastewater treatment through the use of bacteria and fungi. The study highlights how microbial solutions offer sustainable and cost-effective alternatives to traditional chemical treatments. Key methods such as bioaugmentation, bioremediation, and mycoremediation are analyzed for their efficiency in removing pollutants and restoring water quality. The article also presents successful case studies demonstrating the practical application of biotechnology in improving environmental sustainability.